The Accuracy of Postpartum Blood Loss Estimation Using Plastic Collector Bag and Visual Estimation at Ramathibodi Hospital - Phaikaew, Sirikanya; Ploungbunmee, Sophaphan (Ramathibodi Medical Journal, 2019)
Background: Postpartum hemorrhage is a common cause of maternal death. Accurate estimation of postpartum blood loss is important to help parturients before crisis. Objectives: To compare estimation of postpartum blood loss and proportion of postpartum hemorrhage between plastic collector bag and visual estimation. Methods: This study is quasi-experimental design. Participants were 20 singleton parturients, gestational age at 34 - 40 weeks and without complications during pregnancy who delivered at Ramathibodi Hospital. T test was used for comparing the difference of blood loss with Fisher exact test employed for calculating the proportion of parturients postpartum hemorrhage. The Bland-Altman method was used to determine the level of agreement between methods. Results: Postpartum blood loss collected via a plastic collector bag was significantly more than the visual estimation (P < .05). The mean difference of postpartum blood loss between 2 methods was 112.25 with 95% confidence limits of agreement between -212.15 and 436.66. Conclusions: The plastic collector bag was more accurate in blood loss assessment than visual estimation. It can provide early care and prevention of complications that may occur with parturients.